2019
DOI: 10.17951/ijsr.2018.7.0.161-178
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Factors Responsible for Schooling without Learning in Primary and Secondary Schools in Nigeria

Abstract: <p><span style="font-family: TimesNewRomanPSMT; font-size: 9pt; color: #231f20; font-style: normal; font-variant: normal;">The most often debated topic among stakeholders in education and the generality of Nigerians<span style="font-family: TimesNewRomanPSMT; font-size: 9pt; color: #231f20; font-style: normal; font-variant: normal;"> today is the issue of decline in the quality of education at all levels (primary, secondary and<span style="font-family: TimesNewRomanPSMT; font-size: 9pt; co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The finding agrees with some earlier studies that the availability of school facilities is related to students' motivation (Sidi, 2019) and learning outcomes (Arshad et al, 2018;Takwate, 2018). The findings of this study also align with an earlier study which documents an important link between administrative expenditures and students' learning outcomes (Strickland, 2021). Moreover, an earlier study also documented that school curricula changed students' attitudes (Cantoni et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding agrees with some earlier studies that the availability of school facilities is related to students' motivation (Sidi, 2019) and learning outcomes (Arshad et al, 2018;Takwate, 2018). The findings of this study also align with an earlier study which documents an important link between administrative expenditures and students' learning outcomes (Strickland, 2021). Moreover, an earlier study also documented that school curricula changed students' attitudes (Cantoni et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…A case was also presented by the finding of Gigliotti and Sorensen (2018) that sustained financial investment in schools was crucial for districts to maintain quality public education. Even though school financing and administrative expenditures are important predictors of students' learning outcomes (Bruce et al, 2019;Strickland, 2021), the link is known for the cognitive aspect of students' learning outcomes. There seems to be no existing study connecting principals' administrative expenses to students' affective and psychomotor learning outcomes.…”
Section: Studies On Administrative Expensesmentioning
confidence: 99%
“…All stakeholders are concerned about why the system is turning out students with poor results. Authors (Ogunsaju, 2004;Owoeye and Olatunde, 2011;Bertoni et al, 2017;Taylor et al, 2017;Ibrahim et al, 2017;Suleiman et al, 2019) states that the academic standard in all Nigerian educational institutions has fallen considerably below societal expectations. Blumende (2001) corroborated this view when he reported that the decline in the quality of education could not be ignored by anyone aware of the significant role of education as an instrument of societal transformation and development.…”
Section: Introductionmentioning
confidence: 99%